Perceptual Bias in Tabligh Communication on the TikTok Account Megaputriaulia0911 - Aprilia, Rizky; Azizah, Maulida; Aisy, Rihhadul; N, Nasichah (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study examines perceptual bias in tabligh communication on the TikTok account @megaputriaulia0911, a preacher who was previously known as a television soap opera actress. The background of this research stems from the phenomenon of public figures transitioning into the role of preachers without clear religious scholarly credentials, yet gaining significant attention through social media branding. This situation generates differing perceptions among audiences: some appreciate it as a form of hijrah and modern da‘wah, while others question the authority and legitimacy of the messages conveyed. The purpose of this study is to analyze the forms and factors contributing to perceptual bias in tabligh communication conducted by public figures through digital platforms. The research employs a qualitative method, utilizing in-depth interviews with several followers of the account and content analysis of uploaded da‘wah videos. The findings indicate that perceptual bias arises from an imbalance between the religious image constructed through branding and the depth of the da‘wah content delivered, as well as the strong influence of the preacher’s background as an artist. In conclusion, the credibility of the communicator is a key factor in the effectiveness of tabligh communication on social media. This study contributes to an understanding of the challenges of digital da‘wah, particularly regarding the role of public figures in maintaining the authenticity and scholarly integrity of religious messages in virtual spaces.